1994
DOI: 10.1177/104420739400500201
|View full text |Cite
|
Sign up to set email alerts
|

The Underachievement of Supported Employment

Abstract: A review of the status of the national supported employment initiative shows that thousands of individuals are benefiting from the initiative and that supported employment is offered by community programs in every state in the nation. Yet despite these successes, access to supported employment is severely limited, the quality of the outcomes is challenged, and the investment in change appears to be dwindling. If supported employment for persons with severe disabilities is to expand and improve to meet the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…There was no national picture of individuals served across these sectors, of changes in both service sectors since 1986, or of anticipated future changes. Other researchers have suggested that little change has occurred, that integrated employment has merely been added to the existing service continuum as a complement to instead of a replacement for facility-based services, and that the Supported Employment Initiative represents an underachievement with respect to its articulated goals (Agosta, Brown, & Melda, 1993;Albin et al, 1994;Mank, 1994;Wehman & Kregel, 1994).…”
mentioning
confidence: 97%
“…There was no national picture of individuals served across these sectors, of changes in both service sectors since 1986, or of anticipated future changes. Other researchers have suggested that little change has occurred, that integrated employment has merely been added to the existing service continuum as a complement to instead of a replacement for facility-based services, and that the Supported Employment Initiative represents an underachievement with respect to its articulated goals (Agosta, Brown, & Melda, 1993;Albin et al, 1994;Mank, 1994;Wehman & Kregel, 1994).…”
mentioning
confidence: 97%
“…Much has been written within the business literature about the importance of changing behavior as a precursor and a stimulus to changing values rather than vice versa (Beer, Eisenstat, & Spector, 1990;Marrone, Hoff, & Gold, 1999). Welfare reform has had a more drastic effect on how welfare (especially TANF) services are delivered than evidence based practice in mental health (Sanderson, 2002) or supported employment generally in the disability world (Mank, 1994) has had on their respective service systems. Many advocates argue that rehabilitation services that focus on employment are medically necessary (and therefore Medicaid reimbursable) particularly if they remedy the sequelae of mental illness to obtain functioning.…”
Section: Supported Employment Technology Transfermentioning
confidence: 99%
“…However, at least some proponents have maintained that the initiative needed to establish stability in individual outcomes can be achieved by restructuring the systems that support these individuals (Bellamy et al, 1988;Mank, 1994). Recent articles have questioned the extent to which systemic change is occurring (Davis, 1993;Mank, 1994;Wehman & Kregel, 1996).…”
mentioning
confidence: 95%